Filipino Rehabilitation Practitioners’ COVID-19 knowledge, practice and attitude: A cross-sectional study - Grace A.F.I. Rivera; Johann A.P. Querijero; Benjamin G.C. Gilbuena; Alfred A.M. Angulo; Consuelo B. Gonzalez-Suarez; Ma. Arlene L. Ledesma; Jan-Tyrone C. Cabrera; Ivan N.B. Gomez; Gilmore C. Senolos; Maria R.C. Espinosa; Raul M. Cembrano (Rehabilitation Advances in Developing Health Systems, 2024)
Background: The rehabilitation team, consisting of physiatrists, physical and occupational therapists, and speech pathologists, faces heightened risk of COVID-19 exposure because of treatment practices in rehabilitation settings.